Exploring gamma brainwave oscillations during passive listening to melodious recitation of ayatul kursi using simultaneous EEG and MEG recording technique - Abdullah, Mohd Waqiyuddin (2021)
Studies on the effects of Quranic have been focusing on low frequency brainwaves i.e. theta and alpha, the neural candidates indicating calmness and relaxation effects induced from listening to Quranic recitations. The present study examined the high frequency i.e. gamma brainwaves (30-80 Hz), previously unexplored in Quranic recitation studies. Gamma waves have been postulated to play important roles in high cognitive functions such as attention and working memory. Recent studies on non-Islamic approach of meditation had shown an increment of gamma activities among expert meditators, thus higher attention stimulated compared to the novices. In Islam, the concept of meditation can be best explained by Al-Muraqabah, a practice to be self-aware of Allah’s existence which is linked to the act of reciting and listening to Quranic recitations. In the present study, 30 healthy participants from dual faith groups (n Muslim = 15, n non-Muslim = 15) were randomly recruited. By using electroencephalography (EEG) and magnetoencephalography (MEG) techniques, participants were subjected to passive listening of six different auditory stimuli. The stimuli were three different Quranic recitation styles (Murattal Asim Hadr, Murattal Asim Tadwir and Murattal Asim Tahqiq), two non-Quranic (Arabic poem and Arabic news), and one without any stimulus (i.e. resting state). All stimuli were presented randomly for three minutes each and a minute gap in between. Acoustic features of the auditory stimuli including rhythm, stress and pitch were analyzed with Praat software. From the duration analysis of syllables, it was shown that Quranic recitations contained irregular rhythmic structure unlike Arabic poem which had regular rhythm. All Quranic recitations and Arabic poem also contained high intensity and rise-fall pitch pattern from the spectrogram and pitch contour analysis, opposite to Arabic news which had both but with rapid fluctuations. Next, the recorded raw EEG-MEG signals from the brain responses were pre-processed and analyzed using Brainstorm software. Volume sources of gamma wave oscillations were estimated from the selected regions of interest (ROIs). In the presence of auditory stimuli, compared to resting state, wider distributions of gamma activities were observed such as prefrontal cortex (PFC) and parietal areas for both groups that could reflect higher attention, as well as memory process. The magnitude of gamma oscillations from resting state was measured to observe pattern of gamma fluctuations during the presentation of auditory stimuli. Several deep brain ROIs demonstrated higher gamma activities from listening to rhythmic recitations of Ayatul Kursi, depicting that emotion maybe involved. The areas included PFC for both groups, anterior cingulate cortex (ACC) and midcingulate cortex (MCC) for Muslim group and posterior cingulate cortex (PCC) for non-Muslim group. From mix ANOVA analysis, there were no statistically significant interactions found between independent variables i.e. different religious groups and different auditory stimuli on relative gamma power. However, from EEG recordings, significantly higher relative gamma power was recorded in Muslim group than non-Muslim group for all auditory stimuli. Meanwhile, data from MEG recordings revealed significant effects of different auditory stimuli on relative gamma power within several ROIs, including ACC, PFC, amygdala, hippocampus, parahippocampal and parietal lobe. To conclude, the acoustic features of rhythmic recitations of Al-Quran made them comparable with the characteristics of music or singing, in which listening to the rhythmic recitations affect gamma activities in regions related to attention, memory and emotion.